(untitled) (Research, Society and Development, 2020)
This study aims to evaluate through the scientific literature the prevalence of women diagnosed with HIV/AIDS in Brazil between the years 2010 to 2019. It is a bibliographic and retrospective study, in which a research was carried out in the databases. electronic data from SciELO and data from the Ministry of Health’s information system using the descriptors "HIV/AIDS", "sexuality", "gender" and "woman". The number of women in Brazil is higher than that of men, corresponding to 51.7%. However, reports of HIV/AIDS are lower for females as compared to males in the country. Women have a higher probability of HIV contamination, in heterosexual relationships, due to factors such as a greater area of exposure of the vaginal mucosa to seminal fluids and a greater amount of fluids that are transferred from men to women at the time of sexual intercourse. It is necessary to implement public policies in the institutions to encourage reading and knowledge about power, sex and the prevention of sexually transmitted diseases, in addition to the development of new research on the subject, in order to elucidate the means of transmission and ways of preventing the disease.